The effect of soil tillage system and weeding time on the growth of weed and yield of soybean (Glycine max (L.) Merril) - Husni Thamrin Sebayang; Apreza Pallevi Rifai (Brawijaya University, 2018)
The growth and yield of soybeans can decrease due to competition from weeds. Various efforts have been made to control the growth of weeds such as land preparation and weeding periods. An experiment to study the effect of soil tillage systems and weeding time on the growth of weeds and soybean crop yield (Glycine max (L.) Merril) has been done in Wringinsongo Village, Tumpang Sub-District, Malang Regency from February to May 2017. The split-plot design with three replicates was used with the soil tillage system as the main plot consisting of three levels, T0: no tillage, T1: minimum tillage, and T2: conventional tillage, and weeding time as the sub plot consisting of 4 levels, P0: no weeding, P1: weeding 1 time, P2: weeding two times and P3: weeding three times. The results showed that the dominant weed species before treatment were Amaranthus spinosus (Spiny amaranth), Cynodon dactylon (Bermuda grass), Cyperus rotundus (Purple nutsedge), Ageratum conyzoides (Billygoat weed), and Portulaca oleracea (Common purslane). After treatment, the dominant weed species were Cyperus rotundus (Purple nutsedge), Amaranthus spinosus (Spiny amaranth), Ageratum conyzoides (Billygoat weed), Physalis peruviana (Cape gooseberry), and Eclipta alba (False daisy). There was no significant difference of the dry weight of weeds in conventional tillage followed by weeding 3 times at 15, 30 and 45 days after planting, and minimum tillage and no tillage. For the yield of soybeans, conventional tillage followed by weeding 3 times at 15, 30 and 45 days after planting were not significant with that of minimum tillage. The yield of soybeans was lower than that of with no tillage and no weeding.